Cancer Cell Membrane Camouflaged Mesoporous Silica Nanoparticles Combined with Immune Checkpoint Blockade for Regulating Tumor Microenvironment and Enhancing Antitumor Therapy - Zhao P (Dove Medical Press, 2021)
Peiqi Zhao, Lihua Qiu, Shiyong Zhou, Lanfang Li, Zhengzi Qian, Huilai Zhang Department of Lymphoma, Tianjin’s Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, National Clinical Research Center for Cancer, Tianjin Medical University Cancer Institute and Hospital, Tianjin Medical University, Tianjin, 300060, People’s Republic of ChinaCorrespondence: Huilai ZhangDepartment of Lymphoma, Tianjin Medical University Cancer Institute and Hospital, 24 Huanhu West Road, Hexi District, Tianjin, 300060, People’s Republic of ChinaTel +86-22-23340123Email zhlwgq@126.comPurpose: Although anti-programmed cell death protein 1 antibody (aPD1) immunotherapy and chemotherapy has made much progress in the treatment of melanoma, the efficacy still needs to be further improved.Methods: Cancer treatment has been greatly enhanced by the use of nanotechnology. Cancer cell membrane (CCM)-camouflaged nanoparticles have shown promising potential in tumor therapy due to their excellent homologous-targeting ability, long blood circulation and immune escape. This work presents a biocompatible and tumor acidic environmental responsive CCM-camouflaged mesoporous silica nanoparticle (CMSN) that is loaded with dacarbazine (DTIC) and combined with aPD1 to achieve better antitumor efficacy.Results: In vitro cell experiments demonstrated that DTIC@CMSN exhibits a better anti-tumor killing efficiency and a stronger ability to promote the apoptosis of tumor cells than free DTIC. In vivo antitumor results demonstrated that combination therapy of DTIC@CMSN chemotherapy and aPD1 immunotherapy remarkably suppress the melanoma growth and prolong survival time due to highly selective tumor killing, activation of tumor-specific T cells, and regulation of the immunosuppressive tumor microenvironment. In addition, safety evaluation studies of DTIC@CMSN also demonstrate their increased tumor accumulation and decreased systemic toxicity.Conclusion: This study provides a promising nano-platform for the combination of chemotherapy with immunotherapy, which is potentially useful for the treatment of melanoma.Keywords: anti-PD-1, cancer cell membrane, cancer immunotherapy, melanoma, mesoporous silica nanoparticle